MUALAF SEBAGAI MUSTAHIK ZAKAT PERSPEKTIF MUHAMMADIYAH DAN NAHDLATUL ULAMA KOTA PALU - Musdalifa, Aisya; B, M. Taufan; Mayyadah (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
Islam teaches the importance of zakat as one of the main instruments in distributing wealth and upholding social justice. In Qur'an verse At-Taubah 60 explains eight groups of zakat mustahik, one of which is converts, namely people who have just converted to Islam or individuals whose hearts are expected to be attracted to Islam. This research uses empirical research methods, data collection techniques through observation, interviews and documentation studies. The results of the research show that converts to Islam in Palu City have on average embraced Islam for a long time. The picture of converts as zakat recipients is that there are still those who still receive their zakat and there are also those whose zakat has been cut off and has even become muzakki. Giving zakat really helps them and can increase their faith in Islam. The perspective of Muhammadiyah and Nahdlatul Ulama in Palu City refers to At-Taubah 60, which states that converts have the right to receive zakat. The two organizations do not have differences of opinion regarding the criteria for converting zakat recipients, the purpose of giving zakat, the impact of giving zakat from an economic and spiritual perspective, as well as the priority scale for giving zakat. However, they differ in their opinions regarding the time limit for giving zakat to converts. From the conclusions obtained, it is recommended that Muhammadiyah and Nahdlatul Ulama in Palu City have data on converts who receive zakat, so that well-documented data will provide a clear picture of the number of converts, their needs, and the impact of the zakat assistance given to them.